Identity politics of difference : the mixed-race American Indian experience - Montgomery, Michelle R. (University Press of Colorado, 2017)
"A multidisciplinary approach to questions of identity construction and multiracialism through the experiences of mixed-race Native American students at a tribal. Explores the multiple ways in which students navigate, experience, and understand their racial status and how this affects their educational success and social interactions"--Provided by publisher